Ultrafast demagnetization of Pt magnetic moment in L10-FePt probed by magnetic circular dichroism at a hard x-ray free electron laser - Kohei Yamamoto; Yuya Kubota; Motohiro Suzuki; Yasuyuki Hirata; Karel Carva; Marco Berritta; Kou Takubo; Yohei Uemura; Ryo Fukaya; Kenta Tanaka; Wataru Nishimura; Takuo Ohkochi; et al. (New Journal of Physics, 2019)
Unraveling the origin of ultrafast demagnetization in multisublattice ferromagnetic materials requires femtosecond x-ray techniques to trace the magnetic moment dynamics on individual elements, but this could not yet be achieved in the hard x-ray regime. We demonstrate here the first ultrafast demagnetization dynamics in the ferromagnetic heavy 5d-transition metal Pt using circularly-polarized hard x-rays at an x-ray free electron laser (XFEL). The decay time of laser-induced demagnetization of L1 _0 -FePt is determined to be ${τ }_{{\rm{Pt}}}=0.61± 0.04\,{\rm{ps}}$ using time-resolved x-ray magnetic circular dichroism at the Pt L _3 edge, whereas magneto-optical Kerr measurements indicate the decay time for the total magnetization as ${τ }_{{\rm{total}}}\lt 0.1\,ps$ . A transient magnetic state with a photo-modulated ratio of the 3d and 5d magnetic moments is demonstrated for pump–probe delays larger than 1 ps. We explain this distinct photo-modulated transient magnetic state by the induced-moment behavior of the Pt atom and the x-ray probing depth. Our findings pave the way for the future use of XFELs to disentangle atomic spin dynamics contributions.